Hyperostotic Esthesioneuroblastoma - Ramanathan, Murugappan (2013)
Esthesioneuroblastomas are rare, soft-tissue tumors that can often extend from the sinonasal cavity into the intracranial and orbital space. Prognosis depends upon the histological grade and location/extent of the tumor. Treatment often consists of maximum surgical resection followed by adjuvant chemoradiation therapy. We present a case of a patient with esthesioneuroblastoma accompanied by an extensive osteoblastic reaction leading to significant hyperostosis along the skull base. His presenting symptoms included diplopia, and imaging revealed invasion of the orbital and intracranial spaces. Although a gross total resection of the soft tissue component of the tumor was achieved, a complete removal of the involved hyperostotic skull base could not be performed despite endoscopic endonasal and bifrontal craniotomy approaches in the same operative setting. Symptomatically, the patient improved and went on to receive chemoradiation therapy; he remains clinically and radiographically stable at 12 months. Investigation into the genetics and immunohistochemistry of this rare, hyperostotic variant of estheioneuroblastoma may provide details regarding its aggressive nature.